Development of electrospun-based polyetherimide fibers and diameter analysis for potential use in dental materials - Kukulka, Elisa Camargo [UNESP]; Sato, Tabata Prado [UNESP]; Archangelo, Karen Cristina [UNESP]; Santos, Jéssica Dias [UNESP]; De Souza, Joyce Rodrigues [UNESP]; Borges, Alexandre Luiz Souto [UNESP] (Editora Cubo, 2021)
Objetives: this study aimed to fabricate electrospun-based polyetherimide (PEI) fibers, under controlled parameters, and to perform a diameter analysis for potential mechanical improvement of dental materials. Material and Methods: PEI pallets (0.75 g) were dissolved in 2 mL of chloroform and then processed by electrospinning, under a flow rate of 1mLh- 1, three different electrical voltages (10kV, 15kV and 20kV) and three distances (10 cm, 15 cm and 18 cm) between the needle tip and collector. These parameter combinations resulted in nine experimental groups that were analyzed using scanning electron microscopy (SEM) and image processing program for diameter measurement. Statistical analysis was performed using two-way ANOVA with post-hoc Tukey (5% significance). Results: from SEM images it was possible to observe formation of solid, misaligned and flawless defect-free fibers. And from the statistical analysis, distance (p = 0,0026) and the electric tension (p = 0,0012) showed a significant difference, but not for interaction between then (p = 0,4486). Conclusion: thus, it can be concluded that there is a possibility of the morphology control of PEI electrospun fibers, such as diameter, that can be used for a variety of applications such as incorporation in dental materials in order to improve its properties.
Desenvolvimento de fibras de polieterimida à base de eletrofiação e análise de diâmetro para uso potencial em materiais odontológicos
Keywords: Electrospinning technique; Fibers; Polyetherimide; Polymer